Promoting Social Emotional Learning in a School Context (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the importance of promoting Social Emotional Learning (SEL) within a school context. It highlights effective strategies such as integrating SEL into the curriculum, implementing specific SEL programs like "Second Step," and creating a supportive environment that fosters respect and inclusion. The piece also emphasizes the necessity of professional development for educators, the involvement of families in SEL initiatives, and the role of student leadership in promoting emotional wellness. Together, these strategies create a comprehensive approach to SEL, benefiting students' emotional and social development while enhancing academic performance and well-being. The article calls for schools to prioritize these strategies to nurture well-rounded individuals prepared for the complexities of life. By adopting a multi-faceted approach, schools can enhance students' emotional intelligence, resilience, and interpersonal skills, ultimately leading to improved academic performance and overall well-being.